Economic mechanism of costs production management - Skryhun, Natalya; Semenenko, Katerina; Vlasenko, Ludmila (My University, 2012)
The elements of economic mechanism of costs production management are concretized. The main points of costs production management system in the enterprises are described; emphasized the basic functions and principles of costs management production.
Keywords: the system of costs production management; economic mechanism; costs; costs of production; costs production management; менеджмент цінового виробництва; ціна; економічний механізм; ціна виробництва; менеджмент ценового производства; цена; экономический механизм; цена производства; кафедра ділової іноземної мови та міжнародної комунікації; кафедра маркетингу